How to Align the University Curricula with the Market Demands by Developing Employability Skills in the Civil Engineering Sector - Livia Anastasiu; Alexandra Anastasiu; Mihaela Dumitran; Codruţa Crizboi; Alexandra Holmaghi; Maria Nicoleta Roman (MDPI AG, 2017)
The purpose of the research is to discover which employability skills may be developed by students from technical universities in order to meet market demands. Since graduates from technical universities face unemployment or over qualification for vacant jobs, we presumed that there is a misalignment between employers' expectations concerning graduates' skills and what they really get from school. Therefore, we conceived a questionnaire to see the demands of the business environment regarding graduates' technical and professional skills. After analyzing the data, we proposed an interdisciplinary module system, where the mentors coming from the companies involved in the study teach voluntary or optional courses and applications in the domains where they have expertise. We used the employability skills model to find that mix of competencies that may help graduates find jobs in their field of knowledge. This innovative method serves universities, students and companies as well: the prestige of a university is quantified by the experts delivered into the labor market; companies will have well prepared employees in their specific area, with less costs; students will find jobs which will match their expectations, giving them motivation to perform. The limitation of the present research is that the study refers only to the Civil Engineering specialization of the Technical University Cluj-Napoca Romania.